Analysis of effective work per stroke in aquatic locomotions - Kleshnev, V. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Average speed (V), stroke rate (SR) and stroke distance (SD) are fundamental variables of aquatic locomotions, such as swimming, rowing and canoeing. Relationships between these variables are defined by a number of factors, such as the athlete anthropometry, body composition and training methodology. Speed of locomotion V is a product of SR and SD. SR and SD are reversely proportional at the constant V. When athletes increase SR, SD is always decreases, because the time of the cycle T became shorter. Quite often coaches ask athletes to maintain constant SD at higher SR, which never happens in practice. The main target is maintaining efficiency, force application and amplitude of movement. Effective work per stroke (eWPS) is a product of these three factors and should be focused for improving performance. A method was developed for evaluation of relative eWPS by means of analysing V and SD at various SR during aquatic locomotion. The method is based on equation Fd = kV2, which describes dependence of hydro-dynamic drag force Fd on velocity V and drag resistance factor k. This limits applications of the method only to cases, where k is constant (the same athlete/crew in the same conditions). Equality of the eWPS at various stroke rates was taken as a criterion for evaluation. Two equations were developed for calculation of a target speed Vt =V0(R1/R0)(1/3) and SDt = SD0(R0/R1)(2/3). Ratio of the actual values to the target was used for evaluation of the consistency of eWPS: if real V/SD were higher than Vt/SDt, then eWPS was relatively higher and vise versa. The method was verified using biomechanical measurements in rowing, when mechanical work per stroke was measured directly. Forces on the oar handle were measured using strain-gauge transducer mounted on the oar shaft. Oar angles were measured using conductive-plastic potentiometer mounted on the top of the pin. Boat velocity was measured using a turbine mounted underneath the hull. Total number 294 crews in all boat types were measured and 1444 data samples collected. It was found that eWPS derived using the developed method correlates very well (r=0.82) with eWPS measured directly. The method can be successfully used for race analysis in cyclic aquatic locomotions. It can be employed for evaluation of the strength- and speed-endurance using step-test in cyclic water sports. Developed spreadsheets are simple enough to be used by coaches in every day training.